Using IT/ICT as a new medium toward implementation of interactive architectural communication cultures - Rahimian, Farzad Pour; Ibrahim, Rahinah; Baharuddin, Mohd Nasir (IEEE, 2008)
Design is a multi-aspect, iterative, and complicated exclusive human activity and a critical aspect of many modern industries. The early phases of design are drastically affected by quality of communications among process stakeholders. Communication culture within every society depends on the tools people use for their communicational transactions. Today globalization and advanced IT/ICT technologies revolutionized communication culture in every society. We can see extreme changes in product design in the architectural design process. So understanding the situation of design culture dealing with IT/ICT seems vital. This paper contributes with an overview of the current situation of IT/ICT related benefits and challenges due to several aspects of the design process and culture. Explored key points here, establish the background for the introduction of an IT/ICT impact on the design collaboration culture. Conclusions outline the new design interaction culture and the IT/ICT related impacts on different phases of the architectural design process.